POLA KOMUNIKASI KELUARGA MAHASISWA PERANTAU DALAM PENCEGAHAN PERILAKU MENYIMPANG (STUDI KASUS DI KOTA MEDAN, SUMATERA UTARA) - Nida Fadlilah; Yuliandre Darwis (Departemen Ilmu Komunikasi Universitas Andalas, 2026)
This study aims to analyze the communication patterns of long-distance families as a preventive measure against deviant behavior among college students living away from home in Medan, as well as to examine the use of digital media and prevention strategies. This study employs a constructivist paradigm and a qualitative case study method. Data were collected through in-depth interviews with 9 students and 8 parents in Medan and North Sumatera. Data analysis in this study was conducted using NVivo 15. Data validity was assessed using source triangulation. The results indicate that the primary challenges for migrant students in Medan are social circles and a hedonistic lifestyle. Family communication patterns were dominated by the consensual type (high conversation and high conformity), although the protective type (low conversation, high conformity) was also observed in two informants. The use of digital media via the WhatsApp app served as the primary means of long-distance communication, particularly the use of video call features. In the practice of long-distance communication, the comfort and quality of messages were more important than the frequency of communication. Prevention strategies focus on providing advice regarding self-discipline, promiscuity, and anti-hedonism. It is concluded that communication patterns supported by openness, religious values, and close parent-child relationships effectively serve as a social control mechanism in preventing deviant behavior in the host environment.